3.12 Mesolithic middens and marine molluscs, procurement and consumption of shellfish at the site of Sand (Scottish Archaeological Internet Reports, 2009)
The preconceptions that shellfish represent a time of poverty and hardship contrast strongly with the luxury role of shellfish in today's culture. Rather than using modern perceptions to view the consumption practices of the past, it is perhaps more useful to consider the ways in which people were procuring and consuming foods in the past and reflect on the variety and richness of resources that would have been available to them. In the case of Sand, we can see that shellfish were an integral part of life; not only as a raw material but also as part of a rich and varied diet which also included other marine species such as crab and fish, terrestrial animals and, no doubt, plants.